Isolation and characterization of components responsible for neuroprotective effects of Allium cepa outer scale extract against ischemia reperfusion induced cerebral injury in mice. Issue 11 (14th October 2020) - Singh, Varinder; Shri, Richa; Krishan, Pawan; Singh, Inder Pal; Shah, Purvi
Abstract: The antioxidant‐mediated neuroprotective effect of Allium cepa outer scale extract (ACE) in mice with cerebral ischemia‐reperfusion (I‐R) injury was demonstrated in our earlier work. The current investigation aimed at establishing the bioactive component(s) responsible for this activity. Thus ACE was fractionated into ethyl acetate (EF) and aqueous (AF) fractions. These fractions were evaluated against cerebral I‐R injury in mice. I‐R injury in mice was induced by bilateral common carotid artery occlusion followed by 24 hr reperfusion. Memory, sensorimotor functions, cerebral infarct size, and oxidative stress were measured to address the neuroprotective mechanism of test substances. EF showed marked improvement of memory and sensorimotor functions by reducing brain oxidative stress and infarct size in mice after I‐R injury. The bioactive EF was subjected to chromatographic (HPLC‐PDA, HPLC‐MS, preparative HPLC) and spectroscopic studies to isolate and identify the neuroprotective compounds. This lead to separation of three components, namely quercetin, quercetin 4′‐O‐glucoside, and the remaining fraction, from EF. The separated components were biologically evaluated. These components showed improvement in mice with I‐R injury. But, EF displayed more marked neuroprotective effects as compared to the isolated components. The distinct neuroprotective outcome of EF may be credited to the synergistic action of compounds present in EF. Further studies such as evaluation of neurotoxic effects and other possible neuroprotective mechanisms are required to develop EF as a neuroprotective drug.